Expression and integrated network analyses revealed functional divergence of NHX-type Na+/H+ exchanger genes in poplar - Fengxia Tian (Nature Portfolio, 2017)
Abstract The Na+/H+ antiporters (NHXs) are secondary ion transporters to exchange H+ and transfer the Na+ or K+ across membrane, they play crucial roles during plant development and stress responses. To gain insight into the functional divergence of NHX genes in poplar, eight PtNHX were identified from Populus trichocarpa genome. PtNHXs containing 10 transmembrane helices (TMH) and a hydrophilic C-terminal domain, the TMH compose a hollow cylinder to provide the channel for Na+ and H+ transport. The expression patterns and cis-acting elements showed that all the PtNHXs were response to single or multiple stresses including drought, heat, cold, salinity, MV, and ABA. Both the co-expression network and protein-protein interaction network of PtNHXs implying their functional divergence. Interestingly, although PtNHX7 and PtNHX8 were generated by whole genome duplication event, they showed significant differences in expression pattern, protein structure, co-expressed genes, and interacted proteins. Only PtNHX7 interact with CBL and CIPK, indicating PtNHX7 is the primary NHX involved in CBL-CIPK pathway during salt stress responses. Natural variation analysis based on 549 P. trichocarpa individuals indicated the frequency of SNPs in PtNHX7 was significantly higher than other PtNHXs. Our findings provide new insights into the functional divergence of NHX genes in poplar.